THE COMMUNICATIVE FUNCTION AND THE BENEFIT OF CODE SWITCHING WITHIN BILINGUAL EDUCATION PROGRAM OR MULTILINGUAL CHILDREN IN LEARNING ENGLISH - ABDUL MAJID JUNAIDI (LPPM Universitas Gunung Rinjani, 2020)
Though code switching research may vary from context to context and situation to situation, thecommon factors for code switching will be threefold. That is, code switching deals withlanguages in contact. In interactive social situations code switching will be the use of more thanone language. For example the interaction during various social events involving interlocutorswho know more than one language. Gumperz (1982) while discussing the communicativefunction of code switching, claims that the speaker plays upon the connection of the we-code tocreate conversational effect. Thus code switching is seen as fulfilling the relational andreferential functions of language that amounts to effective communication and interlingua unity.As an increasing number of children enter the school, districts are faced with meeting theiracademic needs. These children enter into the classroom with varying language (mothertongue). Some schools have adopted bilingual education programs, teaching subject matter inIndonesian and English. Others believe in immersion, or placing the students in mainstreamclassrooms in which they are expected to learn the English language and subject matter taughtin English simultaneously. Still other schools hover somewhere in between, striving to find thebest way to reach these children/students. What factors can affect/force students to use codeswitching in their discourse? What are the benefits of code switching for L2 children/student?What are the communicative functions of codes switching? These questions are the debate ofbilingual education throughout the country. In this study, explore the effects of difference typesof education such as bilingual education. Specifically, this paper discuss of the role of codeswitching (the use of both Indonesia/Sasak and English within the same discourse) in bilingualsettings.Key words: Communicative function, Code switching, bilingual and multilingual.